IMPLEMENTASI PROSES PENGADAAN PADA JASA LAINNYA MELALUI METODE TENDER DI BAGIAN PENGADAAN BARANG/JASA KOTA SURAKARTA - Nugroho, Salsa Angelina; Ni'mah, Fahmi Ulin (Jurnal Bisnis Administrasi dan Manajemen, 2025)
The purpose of this study is to determine the implementation of other service procurement through the tender method. This study focuses on the selection of providers that apply in BPBJ Surakarta. The selection of providers of goods and services in a government is very difficult because it requires providers of goods and services that meet the requirements that have been set as selection guidelines. The data collection techniques used are interviews, observations, and documentation. BPBJ Surakarta in the tender applies the lowest price with a knockout system. The results of the study indicate that the tender method is carried out online, called e-tendering, to create transparency, efficiency, and effectiveness as well as accountability in the selection of other service providers. This study has a positive influence on participants in other service tenders as preparation for participating in the tender at BPBJ Surakarta, because this study explains the flow from preparation for selecting providers to selecting providers in full.